Aspirin inhibits TGFβ2-induced epithelial to mesenchymal transition of lens epithelial cells: selective acetylation of K56 and K122 in histone H3. Issue 1 (8th January 2020) - Nam, Mi-Hyun; Smith, Andrew J.O.; Pantcheva, Mina B.; Park, Ko Uoon; Brzezinski, Joseph A.; Galligan, James J.; Fritz, Kristofer; Wormstone, I. Michael; Nagaraj, Ram H.
Abstract : Posterior capsule opacification (PCO) is a complication after cataract surgery that can disrupt vision. The epithelial to mesenchymal transition (EMT) of lens epithelial cells (LECs) in response to transforming growth factor β2 (TGFβ2) has been considered an obligatory mechanism for PCO. In this study, we tested the efficacy of aspirin in inhibiting the TGFβ2-mediated EMT of human LECs, LECs in human lens capsular bags, and lensectomized mice. In human LECs, the levels of the EMT markers α-smooth muscle actin (α-SMA) and fibronectin were drastically reduced by treatment with 2 mM aspirin. Aspirin also halted the EMT response of TGFβ2 when introduced after EMT initiation. In human capsular bags, treatment with 2 mM aspirin significantly suppressed posterior capsule wrinkling and the expression α-SMA in capsule-adherent LECs. The inhibition of TGFβ2-mediated EMT in human LECs was not dependent on Smad phosphorylation or MAPK and AKT-mediated signaling. We found that aspirin significantly increased the acetylation of K56 and K122 in histone H3 of human LECs. Chromatin immunoprecipitation assays using acetyl-H3K56 or acetyl-H3K122 antibody revealed that aspirin blocked the TGFβ2-induced acetylation of H3K56 and H3K122 at the promoter regions of ACTA2 and COL1A1 . After lensectomy in mice, we observed an increase in the proliferation and α-SMA expression of the capsule-adherent LECs, which was ameliorated by aspirin administration through drinking water. Taken together, our results showed that aspirin inhibits TGFβ2-mediated EMT of LECs, possibly from epigenetic down-regulation of EMT-related genes.